PERLINDUNGAN HUKUM KONSUMEN PENGGUNA PRODUK MASKER SHISEIDO YANG MENGGUNAKAN BAHASA ASING (STUDI TERHADAP KEMASAN SHISEIDO DALAM BAHASA JEPANG DI WILAYAH TANGERANG) - Rini Yarti; A.M Tri Anggraini (Jurnal Hukum Adigama, 2018)
An imported product to be traded into the territory of Indonesia must include an Indonesian language label in accordance with established regulations, the regulation is regulated in Article 2 paragraph (1) of the Minister of Trade Regulation of the Republic of Indonesia Number 73 / M-DAG / PER / 9/2015 concerning Label Inclusion In Indonesian in Goods. Every product introduced to consumers must be accompanied by correct information. This information is needed so that consumers do not have a wrong picture of the product. This information can be submitted in various ways, one of which is by including an Indonesian translation label on the foreign language label listed on the product packaging. Information on product packaging labels is very necessary for the community so that each individual can correctly determine the choice before buying and consuming the product. In fact there are still many producers who are not responsible for selling cosmetic products that do not meet the requirements. Cosmetic products that do not meet these requirements can be found easily in malls, in traditional markets, or through the internet. The role of the state in this case the government is needed to protect consumers from the circulation of products that do not meet the requirements. So legal protection for consumers is needed to increase awareness of the rights as consumers.